Diagnostic Principles of Peri-Implantitis: a Systematic Review and Guidelines for Peri-Implantitis Diagnosis Proposal - Ausra Ramanauskaite; Gintaras Juodzbalys (eJournal of Oral Maxillofacial Research)
Objectives: To review and summarize the literature concerning peri-implantitis diagnostic parameters and to propose guidelines for peri-implantitis diagnosis.